Teknik Penerjemahan Arab-Indonesia Dalam Teks “Masāil fī al-Śiĥr" dengan Menggunakan Quillbot - Nurul Fitriyah; Maulida Auladina Fadheela EF; Mohamad Zaka Al Farisi; Rinaldi Supriadi (Lingua Franca, 2024)
This study aims to analyze the translation techniques used by QuillBot in translating the text titled "مسائل في السحر" from the book "مسألة في الرقية والعين والمس والسحر ٦٠" by Sulṭān bin 'Abdullāh al-Umri. The research employs a qualitative descriptive method by classifying the translation results based on Molina and Albir's (2002) translation technique theory. The data analyzed include six translation techniques: transposition, reduction, modulation, amplification, calque, and naturalized borrowing. The study's findings reveal that modulation is the most dominant technique, appearing in 5 data points, followed by transposition and reduction, each with 4 data points. Amplification is used in 3 data points, while calque and naturalized borrowing are each applied to 1 data point. The analysis indicates that QuillBot's translations are generally acceptable but still have shortcomings in certain aspects that require human interpretation to maintain the acceptability of meaning. In conclusion, collaboration between translation software like QuillBot and human expertise is essential to produce accurate and contextually appropriate translations.